Circulating white blood cell counts in captive and wild rodents are influenced by body mass rather than testes mass, a correlate of mating promiscuity. (23rd January 2015) - Tian, Jundong; Courtiol, Alexandre; Schneeberger, Karin; Greenwood, Alex D.; Czirják, Gábor Á.; Piersma, Theunis
Summary Comparative studies of captive primates and carnivores have shown a positive correlation between total white blood cell (WBC) counts and the level of inferred mating promiscuity (e.g. using testes mass). This correlation has been interpreted to support the 'sexually transmitted diseases (STDs)' hypothesis, which states that differential spread of STDs is caused by variation in mating behaviour which shapes baseline aspects of the immune system in mammals. In the present study, we tested the STDs hypothesis in rodents using 28 species from free‐ranging and 9 species from captive populations. We compiled data set for the 9 studies of captive rodent populations from the International Species Information System (ISIS) and gathered 136 studies of wild populations from the literature. Using phylogenetic generalized least‐squares statistical models considering non‐independence resulting from shared ancestry, we confirmed that species with greater adult body mass averaged across sexes had elevated total WBC and differential WBC (neutrophils and lymphocytes) counts and that captive animals presented higher lymphocyte counts than free‐ranging ones. However, we found that the total and differential WBC counts did not covary with the residual testes mass – a correlate of mating promiscuity. The results suggest that selection pressures caused by STDs may strongly vary among taxonomic groups. In order to determine the drivers of immunological variation among mammals, further comparative immunological studies including a wide range of taxonomic groups and socio‐ecological variables should be performed and we recommend doing so by primarily focusing on free‐ranging animals.